Concise Review: Prostate Cancer Stem Cells: Current Understanding. (27th August 2018) - Skvortsov, Sergej; Skvortsova, Ira-Ida; Tang, Dean G.; Dubrovska, Anna
Abstract : Prostate cancer (PCa) is heterogeneous, harboring phenotypically diverse cancer cell types. PCa cell heterogeneity is caused by genomic instability that leads to the clonal competition and evolution of the cancer genome and by epigenetic mechanisms that result in subclonal cellular differentiation. The process of tumor cell differentiation is initiated from a population of prostate cancer stem cells (PCSCs) that possess many phenotypic and functional properties of normal stem cells. Since the initial reports on PCSCs in 2005, there has been much effort to elucidate their biological properties, including unique metabolic characteristics. In this Review, we discuss the current methods for PCSC enrichment and analysis, the hallmarks of PCSC metabolism, and the role of PCSCs in tumor progression. Abstract : Prostate cancer development is an evolutionary process that reflects an evolving of prostate cancer stem cells (PCSCs) possessing self-renewal properties and genomic instability. Tumor metastases might be driven by the constantly evolving populations of PCSCs. This is evidenced by the fact that circulating tumor cells (CTCs) and disseminated tumor cells (DTCs) express many PCSC markers, and metastasis-initiating cells (MICs) also share key PCSC features including ability to self-renew, establish tumors and activate PCSC-specific signaling pathways. In this review, we discuss the current methods for PCSC enrichment and analysis, the hallmarks of PCSC biology and the role of PCSCs in therapy resistance, tumor progression and metastases.